Notice of the 'Bluidy Banner' of Drumclog and Bothwell Brig, preserved at Dunbar (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author presents several illustrations of banners used by the Covenanters in the Seventeenth century. He focuses on one banner in particular that he has an unusually thorough provenance for thanks to information he gained from its owners. He uses the discussion of these items to highlight the brutality of the conflict and to raise questions about the reliability of written records from the time.